CLINICAL EPIDEMIOLOGICAL CHARACTERISTICS OF PARKINSON'S DISEASE IN A NATIONAL HOSPITAL OF THE PERUVIAN HIGHLANDS - Condor, Iván R. (2019)
Objective: To determine the main epidemiological and clinical characteristics of Parkinson's disease at the National Hospital "Ramiro Prialé Priale" in Huancayo. Methods: Observational, descriptive retrospective study of a serie of cases. 84 patients were studied between 2015 and 2017, treated in the outpatient clinic or hospitalization of Neurology and Internal Medicine, for which their medical records were reviewed, the sampling was non-probabilistic of the census type selected by the investigator's judgment. Results: The average age was 72.93 years, the male gender prevailed (58.3%), the degree of university education (50%) and the origin of Huancayo (77.4%). Decompensated arterial hypertension was the reason for hospitalization (19.1%), disease time ranged between 1-7 years (57.1%) and tremor at rest and bradykinesia was the most frequent motor symptom (23.8%) In non-motor symptoms, 38.1% had sleep disorders, 21.4% family history of Parkinson's disease and the most associated comorbidities were: depression (48.8%) and insomnia (41.7%). Conclusion: Parkinson's disease is a frequent pathology in older adults and males; The predominant motor symptom is resting tremor and bradykinesia, and the associated neuropsychiatric comorbidities are depression and insomnia.